Statistical Analysis of Magnetic Field Fluctuations in Coronal Mass Ejection-Driven Sheath Regions - Kilpua, E. K. J.; Good, S. W.; Ala-Lahti, M.; Osmane, A.; Fontaine, D.; Hadid, L.; Janvier, M.; Yordanova, E. (Frontiers in Astronomy and Space Sciences, 2021)
We report a statistical analysis of magnetic field fluctuations in 79 coronal mass ejection- (CME-) driven sheath regions that were observed in the near-Earth solar wind. Wind high-resolution magnetic field data were used to investigate 2 h regions adjacent to the shock and ejecta leading edge (Near-Shock and Near-LE regions, respectively), and the results were compared with a 2 h region upstream of the shock. The inertial-range spectral indices in the sheaths are found to be mostly steeper than the Kolmogorov −5/3 index and steeper than in the solar wind ahead. We did not find indications of an f−1 spectrum, implying that magnetic fluctuation properties in CME sheaths differ significantly from planetary magnetosheaths and that CME-driven shocks do not reset the solar wind turbulence, as appears to happen downstream of planetary bow shocks. However, our study suggests that new compressible fluctuations are generated in the sheath for a wide variety of shock/upstream conditions. Fluctuation properties particularly differed between the Near-Shock region and the solar wind ahead. A strong positive correlation in the mean magnetic compressibility was found between the upstream and downstream regions, but the compressibility values in the sheaths were similar to those in the slow solar wind (<0.2), regardless of the value in the preceding wind. However, we did not find clear correlations between the inertial-range spectral indices in the sheaths and shock/preceding solar wind properties, nor with the mean normalized fluctuation amplitudes. Correlations were also considerably lower in the Near-LE region than in the Near-Shock region. Intermittency was also considerably higher in the sheath than in the upstream wind according to several proxies, particularly so in the Near-Shock region. Fluctuations in the sheath exhibit larger rotations than upstream, implying the presence of strong current sheets in the sheath that can add to intermittency.